Evaluation of the Role of the Body's Response to Skin Damage in Experimental Diabetes Mellitus Based on Individual Typological Reactions of the Body (Eurasian Medical Research Periodical, 2023)
In modern experimental diabetology, chemical models of diabetes occupy the first place, and various methods of QD experimental model are used in the field of enteropharmacology. Alloxan diabetes occurs as a result of the use of alloxan in animals, which develops necrotic processes in the pancreas, and then the symptoms of diabetes appear. Modeling of skin defect in animals with different individual typological reactions in experimental diabetes and comparative analysis of skin tissue regeneration in 60 rats. It is planned to divide animals by typological category (groups): "sympathetic-active" and "parasympathetic-active".